Modulatory effects of ethanol extract of Spondias mombin leaves on sodium arsenite induced toxicity (2013)
This study evaluated the ameliorative potential of aqueous extract of Spondias mombin against arsenic-induced toxicity in the rat brain. Forty-five albino rats were randomly divided into nine groups of 5 rats each. Groups A, C and E were administered S. mombin leaf extract alone in graded doses of 100, 200 and 300 mg/kg body weight respectively for 7 days. Groups B, D and F were administered the extract at 100, 200 and 300 mg/kg respectively for 7 consecutive days in a single oral dose by gavaging before oral administration of sodium arsenite (NaAs02) (2.5mg/kg) on day 7. Groups G and H served as the negative control groups and received 0.2 ml diluted propylene glycol (vehicle for the extract) and distilled water respectively. Group I received distilled water for 7 consecutive days and 2.5mg/kg NaAs02 as a single oral dose on the 7th day. Heamatological (packed cell volume, red blood cell count, haemoglobin, white blood cell count, platelets, and neutrophils count) and biochemical parameters (serum alkaline phosphatase, aspartate aminotransferase, alkaline phosphatase, gamma glutamyl transferase) urea and Creatinine were evaluated in all animals. Clastogenecity activity was evaluated by studying micronuclei formation in polychromatic erythrocyte cells in bone marrow. Pretreatment with S. mombin significantly reduced the elevated serum levels of liver enzymes and reduced the frequency of micronucleated polychromatic erythrocytes (MnPCEs) in rat bone marrow intoxicated with arsenic. Histological examinations showed that the extract at tested dosages protected against NaAs02-induced liver damage. Our findings suggest that the leaf extract of S. mombin possesses a remarkable ameliorative effect against sodium arsenite induced toxicity in albino rats.